Dominia Anglorum in America Septentrionali / Specialibus mappis Londini primum a Mollio edita, nunc recusa ab Homannianis Hered (Homann Erbe, (Firm), 1737)
Hand colored.; Relief shown pictorially.; Sheet title in Latin and German. Individual map titles and text in German. Maps in English and German.; Includes text and glossary. Cartographic data A. Newfovndland, od. Terra Nova S. Lavrentii Bay, die Fisch-Bank, Acadia, nebst einem Theil New Schotland.--B. New Engelland, New York, New Yersey und Pensilvania.--C. Virginia und Maryland.--D. Carolina, nebst einem Theil von Florida. Color;